“O que se ouve”, “o que se diz”, por que se diz? : classe trabalhadora e formação escolar de nível médio - Jung, Carine Ane (2014)
This study makes a theoretical analysis about this content in the main criticisms directed towards education of middle level, driven by public school for the young children of the working class, or already in the world of work. These criticisms are desferidas by various sectors of society, including by the working class. Both locally, in the city of Toledo-PR, and nationally, the narratives of the working class in relation to public school and high school claim that this has failed to comply with the social function that has been allocated, therefore the school curriculum that guides this level of education is based on knowledge considered from the truth of students from the working class. We prioritize our research shows "what you hear" at the national level about the education of middle level from surveys conducted by the Getúlio Vargas Foundation (FGV), Brazilian Center for Analysis and Planning (CEBRAP) and Victor Civita Foundation (FVC) , understanding that they represent the dominant thinking about the social function that the school must exercise today and with which we have agreed not. To portray "what is said" in the city of Toledo-PR present the lines of the school community of the State College Senator Attilio Fontana - CESAF, located in a working class neighborhood, in the neighborhood Vila Pioneer, near the company BR FOODS (old Sadia SA ). This work recognizes the current situation of high school audience in Brazil as a reflection of the education system in the country needs urgent educational reform and that has problems, but aims to discuss how to prepare these criticisms made by the working class, since understands there as grounds for their mistaken assumptions formulations, to the extent that they take what is due by origin, what we understand by a materialist perspective, dialectical and historical analysis, constitute an idealistic reversal. The distance experienced by individuals in relation to the laws governing the objects in capitalist society allowed the workers to embrace the educational proposals coming from the ruling class, so while school products and the company is called, expressed through their lines, contrary to imagine how much the school as a social institution is reproducing the social conditions in which it operates. Their narratives show clearly the fact that they have difficulties in unveiling the causal connections that conform to reality, because mostly have no knowledge that are beyond your daily life and allow them to reestablish a relationship between his private life and the universality of gender human. Therefore, their arguments reflect inequalities not only material but also cultural guiding men in a class society.